Democratizing biblical studies: toward an emancipatory educational space - Schüssler Fiorenza, Elisabeth (Westminster John Knox Press, 2009)
Introduction: Toward a radical democratic self-understanding of biblical studies -- Contextualizing arguments for a radical democratic educational space -- Towards a radical democratic pedagogy of biblical studies -- The rhetorical space of graduate biblical studies -- Charting the problem -- The need to transform the discourses of biblical studies -- Proposals for re-visioning biblical studies -- Problematizing the dualistic domain construction of the field of biblical studies -- A republic of many voices : paradigms of biblical studies -- Paradigm criticism -- Redescribing and renaming the paradigms of biblical studies -- Fashioning a radical democratic discourse -- Delineating the fourth emancipatory paradigm -- Discursive struggles within the fourth paradigm : from margin to postcolonialism -- Toward a shared analytic : intersectional analysis of kyriarchy -- A pedagogical model of agency and conscientization -- Changing biblical studies toward a radical democratic pedagogy and ethos -- Transforming malestream pedagogical models -- Toward a radical democratic emancipatory pedagogy -- Transforming the didactic triangle -- Toward a radical democratic ethos - space -- Metalogue : from theory to practice -- Creating a radical democratic seminar space -- A forum of many voices/a kaleidoscope of personal reflections